Community Involvement in Tourism Development: A Case Study of Lenggong Valley World Heritage Site - A. Khadar, Nur Zafirah; Jaafar, Mastura; Mohamad, Diana (EDP Sciences, 2014)
This paper examines the empirical relationship between the economic impact and community involvement in the Lenggong Valley. Recommendations for improvement in development effectiveness through the development of a community centre for economic and social activities, with specific attention given to types of activity and community involvement stimulating the economic development in the Lenggong Valley. Heritage tourism development is a tourism in which arts, culture and heritage form a key attraction for visitors and it can be represented as an area of significant economic benefit to heritage sites. The tourism industry in Hulu Perak became more widespread after Lenggong Valley is recognized as a World Heritage Site. There is shown a positive effect on the development and economic prosperity.